Towards Adaptive Aircraft Landing Order with Aircraft Routes Partially Fixed by Air Traffic Controllers as Human Intervention. Issue 2 (1st March 2018) - Murata, Akinori; Sato, Hiroyuki; Takadama, Keiki
Abstract : This paper focuses on how to reduce the cognitive loads of air traffic controllers while solving the airport landing problem (ALP), which is the optimization of both aircraft landing routes and sequences. A method is proposed for adaptively changing landing sequences by optimization according to routes partially fixed by the controllers as a factor of human intervention. Intensive simulations conducted at Haneda Airport have revealed that the method (1) can maintain the same level of results without needing to fix some of the routes (i.e., the same total distance of all aircraft from their starting positions to the same destination airport) and (2) has much potential for reducing the cognitive loads of controllers by fixing some routes to reduce the number of aircraft that need to be monitored continuously.